Traslado quinhentista do contrato que a Câmara de Évora fez da administração da aposentadoria de Évora com os mesteres (1464) - Pereira, Diogo Alexandre Reis (2022)
1464, Évora, junho, 18 Traslado quinhentista do contrato que a Câmara de Évora fez da administração da aposentadoria de Évora com os mesteres. 1464, Évora, 18 June Sixteenth-century transcript of the contract that the Council of Évora celebrated with the guildsmen regarding the administration of Évora’s aposentadoria.